COMMUNICATION STRATEGIES OF ACCOUNTING STUDENTS IN ENGLISH BUSINESS PRESENTATIONS - Winna Natalia Kristiani Bawamenewi; Lusia Luria Nehe; Anju Lumban Gaol (Journal of Language Education (JoLE), 2026)
Effective communication skills are essential for accounting students, particularly in delivering English business presentations in global professional contexts. However, many students encounter linguistic and cognitive challenges that may hinder their performance. This study aims to analyze the types and functions of communication strategies used by accounting students during English business presentations and to explore the underlying reasons for their use. This study employed a descriptive qualitative design, the study involved 20 undergraduate accounting students. Data were collected through classroom observations, video recordings, and transcription of presentations, and analyzed using the framework of Zoltán Dörnyei. The findings reveal that students employed a range of communication strategies, with compensatory strategies being the most dominant. Fillers (41.0%) and code-switching (30.8%) were the most frequently used strategies, followed by paraphrasing (18.6%) and avoidance (9.6%). These results indicate that students prioritize maintaining fluency and ensuring message clarity, particularly when presenting complex accounting content. While the use of paraphrasing reflects emerging strategic competence, the high reliance on fillers and code-switching suggests limitations in linguistic proficiency and discipline-specific vocabulary. This study highlights the importance of integrating communication strategy training into English for Specific Purposes (ESP) instruction, particularly in accounting education. Enhancing students’ communicative competence requires not only improving language accuracy but also fostering strategic language use in professional contexts. The findings provide pedagogical insights for developing more effective teaching practices that better prepare students for real-world business communication.